Construction of a Conditionally Asporogenous Bacillus thuringiensis Recombinant Strain Overproducing Cry Protein by Deletion of the leuB Gene - Quan, Meifang; Peng, Jinli; Zhu, Zirong; Zhou, Pengji; Luo, Sisi; Xie, Junyan; Xia, Liqiu; Sun, Yunjun; Ding, Xuezhi (Frontiers in Microbiology, 2020)
One of the common shortcomings with Bacillus thuringiensis (Bt) biopesticides in field application is their instability under UV irradiation. In Bt, the leuB gene encodes the 3-isopropylmalate dehydrogenase. In addition to its role in leucine biosynthesis, LeuB would be likely recruited to catalyze the dehydrogenation of malate in the final step of tricarboxylic acid cycle during sporulation. In this study, we constructed a Bt recombinant strain in which the gene leuB was deleted by using the markerless gene deletion system. The ΔleuB mutant strain showed a conditionally asporogenous phenotype while overproducing insecticidal crystal proteins and retaining its insecticidal activity well in both fermentation and LB media. Furthermore, the metabolic regulation mechanisms of LeuB was elucidated by iTRAQ-based quantitative proteomics approach. Evidences from proteomics data suggested that the inhibited supply of pyruvate was an important factor resulting in the conditionally asporogenous feature of the mutant. Consistently, the mutant regained its ability to sporulate in LB medium by adding 1% glucose or 1% sodium pyruvate. Taken together, our study demonstrated that deletion of the leuB gene resulted in delayed or completely blocked mother cell lysis, allowing the crystals encapsulated within cells, which makes this recombinant strain a good candidate for developing Bt preparations with better UV-stability.